Recommendations for assessing motor performance in individuals with dementia: suggestions of an expert panel - a qualitative approach - Trautwein, Sandra; Barisch-Fritz, Bettina; Scharpf, Andrea; Bossers, Willem; Meinzer, Marcus; Steib, Simon; Stein, Thorsten; Bös, Klaus; Stahn, Alexander; Niessner, Claudia; Altmann, Stefan; Wittelsberger, Rita; et al. (European review of aging and physical activity, 2019)
Recommendations for assessing motor performance in individuals with dementia (IWD) are rare, and most existing assessment tools previously applied in IWD were initially developed for healthy older adults. However, IWD and their healthy counterparts differ in motor and cognitive capabilities, which needs to be considered when designing studies for this population. This article aims to give recommendations for motor assessments for IWD and to promote standardisation based on a structured discussion of identified assessment tools used in previous trials.